RNA Interference Technology - Xu, Wei (Comprehensive Biotechnology, 2019)
RNA interference (RNAi) is the biological process of mRNA degradation induced by complementary sequences double-stranded (ds) small interfering RNAs (siRNA) and suppression of target gene expression. Exogenous siRNAs (perfectly paired dsRNAs of ∼21–25 nt in length) play an important role in host defense against RNA viruses and in transcriptional and post-transcriptional gene regulation in plants and other eukaryotes. Using RNAi technology by transfecting synthetic siRNAs into eukaryotic cells to silence genes has become an indispensable tool to investigate gene functions, and siRNA-based therapy is being developed to knockdown genes implicated in diseases. Other examples of RNAi technology include method of producing highly potent and purified siRNAs directly from Escherichiacoli cells, based on an unexpected discovery that ectopic expression of p19, a plant viral siRNA-binding protein, stabilizes a cryptic siRNA-like RNA species in bacteria. Those siRNAs, named as pro-siRNA for “prokaryotic siRNA”, are bacterial RNase III products that have chemical and functional properties that like eukaryotic siRNAs.